Strategy for Improving Public Services of the Buleleng Regency Transportation Office - Kadek Hendra Negara Putra; Putu Indah Rahmawati; Ni Made Ary Widiastini (International Journal of Social Science and Business, 2023)
Public services at the Buleleng Regency Transportation Office require improvement to achieve optimal levels of community satisfaction. The main objective of this study is to formulate a strategy to improve public services at the Buleleng Regency Transportation Office by applying the SOAR method. This study used a qualitative research approach. Data was collected by observation, documentation, focus group discussion (FGD) techniques. To achieve the maximum target, strategies to achieve it include: (1) revitalization of facilities and infrastructure in the field of transportation; (2) make comprehensive planning in order to improve connectivity between regions in Buleleng Regency; (3) increased supervision and control of land, river and lake transportation; (4) the effectiveness and efficiency of managing activities whose budgets are sourced from the District APBD, Provincial APBD and APBN; (5) improve maintenance and coordination in terminal and parking management; (6) synergy with stakeholders in order to improve community discipline in traffic; (7) improving the ability of human resources in the field of transportation; (8) development of information system openness through various social media and information; (9) conduct comprehensive monitoring and evaluation in order to increase regional revenues from the transportation sector; (10) Increased service capacity of the Motor Vehicle Testing Technical Implementation Unit; (11) Imposition of strict rewards and punishments on employees. The results of this research are useful for the local government of Buleleng Regency. This strategy can be used as a reference in the preparation of the roadmap for the development of the Buleleng Regency Transportation Office.